Mapping of quantitative trait locus for resistance to anthracnose in a population derived from genotypes PI 527538 and Ervilha of common bean - Mulube, Mwiinga; Hamabwe, Swivia; Kuwabo, Kuwabo; Chinji, Modreen; Nkandela, Mukuni; Botha, Joseph; Mwense, Brian; Tembo, Langa; Lungu, Davies; Mukuma, Chikoti; Parker, Travis; Kamfwa, Kelvin (Frontiers in Plant Science, 2025)
Anthracnose (ANT) caused by the fungus Colletotrichum lindemuthianum is a major disease of common bean (Phaseolus vulgaris L.). The objectives of this study were to (i) characterize four isolates of C. lindemuthianum into races, (ii) identify quantitative trait locus (QTL) associated with resistance to these four races, and (iii) identify lines with pyramided resistance to the characterized races. The four isolates collected from the major bean-growing region of Zambia were characterized into races 6, 7, 81, and 294. This is the first time that these four races are being reported in Zambia. These races were used to inoculate 220 F5:9 recombinant inbred lines (RILs) derived from a cross between the Andean common bean genotypes PI 527538 and Ervilha. Only two RILs were highly resistant to all four races. Six QTLs were identified on chromosomes Pv01 (ANT1.1), Pv03 (ANT3.1), Pv04 (ANT4.1), and Pv10 (ANT10.1, ANT10.2, and ANT10.3), which conferred resistance to the four characterized races. The R2 of these QTLs ranged from 6.3% to 90.3%, suggesting that both major- and minor-effect loci controlled ANT resistance. Some of the identified QTLs overlapped with previously reported QTLs while others did not. A total of 31 disease resistance genes with NB-ARC-LRR and TIR-NBS-LRR domains were identified as candidate genes for ANT1.1 and ANT10.2. The two RILs with superior resistance to all four races represent a valuable genetic resource to improve the yellow beans for ANT resistance while QTL analysis has provided valuable information to develop a marker-assisted selection strategy for ANT resistance in the yellow bean market class.